(untitled) (Medico Legal Update, 2021)
Cardiovascular emergencies often occur suddenly, delays in treatment cause the condition to worsen. One of the cases of cardiovascular emergency is acute myocardial infarction (AMI). AMI patients must have stable hemodynamics in order to improve their condition. Management of nursing care that can be done to maintain hemodynamic stability of AMI patients is the implementation of Phase 1 Cardiac Rehabilitation. The purpose of this study was to analyze the effect of Phase 1 Cardiac Rehabilitation on Non-Invasive Hemodynamics for Acute Myocardial Infarction Patients in the ICCU Room of Kediri Baptis Hospital. The research design used a quasy experiment one group pre post test design. Population in this study were all AMI patients who were treated in the ICCU Room of the Kediri Baptist Hospital who were taken using a quota sampling technique with a sample size of 35 respondents. The instrument used was an observation sheet including: systolic - diastolic blood pressure and heart rate. Phase 1 cardiac rehabilitation program intervention was carried out for 2 consecutive days, with 2 training sessions/day (morning and evening). Each training session with a duration of 15 minutes. The data analysis of this study used the Paried T-Test statistical test. The results of this study showed that p = 0.026, p = 0.014 p <0.05 and that p = 0.024 p <0.05, which means there is an effect of phase 1 cardiac rehabilitation on cytolic, diastolic blood pressure and heart rate in acute myocardial infarction patients in the ICCU room of Kediri Baptist Hospital. Conclusion Cardiac Rehabilitation Phase 1 has a significant effect on heart muscle function based on the results of blood pressure checks seen from systolic and diastolic and heart rate. Where the greatest significance is on heart rate compared to blood pressure.